Grapevine Subtilase Family: Update on New Sequences and Nomenclature Proposal - Figueiredo, Joana; Maia, Marisa; Sousa Silva, Marta; Figueiredo, Andreia (Frontiers in Plant Science, 2017)
A commentary on Revisiting Vitis vinifera Subtilase Gene Family: A Possible Role in Grapevine Resistance against Plasmopara viticola by Figueiredo, J., Costa, G. J., Maia, M., Paulo, O. S., Malhó, R., Sousa Silva, M., and Figueiredo, A. (2016). Front. Plant Sci. 7:1783. doi: 10.3389/fpls.2016.01783